Investigating the lecturers' acceptance towards the implementation of blended learning in UiTM Pahang / Azniza Ahmad Zaini ...[et al.] - Ahmad Zaini, Azniza; Noradzan, Haslinda; Hussain, Fazlin Marini; Canda, Roger (2013)
Adopting blended learning in teaching and learning is the process of combining the traditional face-to-face instructions and computer mediated instruction. This paper discusses the early investigation on the factors that influence lecturers' acceptance towards the implementation of blended learning in delivering lectures and conducting online assessment to students. Starting February 2013, eight hands-on training sessions have been conducted in Universiti Teknologi MARA (UiTM) Pahang to promote blended learning approach in teaching and learning process. The data on the number of lecturers who attended the hands-on workshop and registered lecturers for blended learning mode were collected from i-Learn Center (i-LeC) UiTM Malaysia. Self-administered questionnaire were distributed to 53 lecturers from various faculties at UiTM Pahang using convenience sampling method and the data was analysed using descriptive statistics. The findings show that majority of the lecturers do accept the implementation of blended learning mode in their teaching and learning process although they are not ready to do so.